Methane Activation and Transformation on Polyoxometalates. (14th January 2013) - Lefebvre, Frédéric; Grinenval, Eva; Putaj, Piotr
Abstract : Methane is activated at moderate temperature on polyoxometalates, leading to the evolution of hydrogen and the formation of a methoxy species which has been characterized by solid-stateC 13 CP-MAS NMR. In the case of a molybdic polyoxometalate, the methyl group is linked to an edge-shared oxygen atom of the polyoxometalate. Upon heating, it reacts with oxygens of the polyoxometalate resulting in the formation of formyl species and then carbon dioxide and a reduction of molybdenum. Upon treatment with water, only traces of methanol can be detected.